Eosinophilic Esophagitis in Children - Tatyana N. Budkina (Voprosy Sovremennoj Pediatrii, 2016)
Eosinophilic esophagitis is a chronic, immune/antigen-mediated esophageal inflammatory disease characterized by a pronounced eosinophilic infiltration of its mucous membrane. The occurrence of eosinophilia and damage of the esophageal mucous membrane is caused by exposure to food and aeroallergens, by genetic predisposition, and by activation of immune responses mediated by T-helper 2. In pediatric, eosinophilic esophagitis is most common in preschool and school-aged children with a burdened allergic history. Clinically, eosinophilic esophagitis is manifested by epigastric pain, symptoms similar to gastroesophageal reflux disease, and dysphagia. Diagnosis of eosinophilic esophagitis is based on clinical symptoms, characteristic endoscopic and morphological changes in the esophageal mucous membrane. The article presents algorithms for examination, dynamic observation and treatment of children with eosinophilic esophagitis, developed by The European Society for Paediatric Gastroenterology Hepatology and Nutrition (ESPGHAN), describes the recommendations for biopsy of the esophageal mucous membrane when eosinophilic esophagitis is suspected. Treatment of children with eosinophilic esophagitis is based on the following approaches: trial treatment by proton pump inhibitors for 2 months, diet correction and, if ineffective, the use of topical corticosteroids.